2015
DOI: 10.1002/cam4.483
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre‐existing mental health comorbidities on the stage at diagnosis and timeliness of care of solid tumor malignances in a Veterans Affairs (VA) medical center

Abstract: There are limited data on the impact of mental health comorbidities (MHC) on stage at diagnosis and timeliness of cancer care. Axis I MHC affect approximately 30% of Veterans receiving care within the Veterans Affairs (VA) system. The purpose of this study was to compare stage at diagnosis and timeliness of care of solid tumor malignancies among Veterans with and without MHC. We performed a retrospective analysis of 408 charts of Veterans with colorectal, urothelial, and head/neck cancer diagnosed and treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…Consistent with our results, two studies in the Veteran Affairs (VA) system, a system providing care to all beneficiaries, did not observe an association between depression and treatment. A recent study in the VA system also did not find differences in the stage at diagnosis or delay in care for colorectal, urothelial, and head and neck cancer between patients with and without mental health problems(57). The authors concluded that mental health is not a barrier to cancer staging or treatment in the VA system that integrated mental health care and routine health care(57).…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our results, two studies in the Veteran Affairs (VA) system, a system providing care to all beneficiaries, did not observe an association between depression and treatment. A recent study in the VA system also did not find differences in the stage at diagnosis or delay in care for colorectal, urothelial, and head and neck cancer between patients with and without mental health problems(57). The authors concluded that mental health is not a barrier to cancer staging or treatment in the VA system that integrated mental health care and routine health care(57).…”
Section: Discussionmentioning
confidence: 98%
“…Patients with SMI encounter barriers to care: for instance, patients with SMI are less likely than those without SMI to receive cancer screening and/or preventive care services . Moreover, cancer patients with SMI are less likely to receive definitive treatment . While numerous studies have examined the treatment and all‐cause survival of prostate cancer patients with low or intermediate grade disease, few if any have compared the treatment and cancer‐specific survival of high‐grade prostate cancer patients with and without SMI.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies, all from the US 15,22,42 explored differences in time from cancer diagnosis to the receipt of cancer treatment between patients with and without PMHD. The first included 408 patients with an axis I mental health disorders (as defined by the Diagnostic and Statistical Manual of Mental Disorders IV, DSM-IV) at least 1 year prior to the diagnosis of colorectal, urothelial, and head/neck cancers.…”
Section: Time From Cancer Diagnosis To Cancer Treatmentsmentioning
confidence: 99%